Tourist Flow and Tourism Potential Regions of Gulmarg in Kashmir Himalayas (Global Journal of Human-Social Science, 2013)
Gulmarg has a rich and diverse touristic product that holds the potential to be one of the most attractive tourist destinations for both leisure and sports tourism across the whole Kashmir Himalayan region. The place owes its importance mainly to its beautiful geoenvironmental setup and unique climate. The destination has a history of tourism activities for more than five centuries. The resort has been a great attraction for several British officials posted in India and their families made Gulmarg their home for the summer months. This his togeographical personality of the place has resulted in the development of tourist regions of interest to a range of tastes especially for holiday makers and sports and adventure tourists. Therefore present study aims at identification and delineation of the different tourist potential regions of the place which would help in proper marketing of the tourist product, management of tourist flow, optimization of economic returns and management of the environmental health of the destination for sustainable tourism development in the region.